Molecular, morphological and acoustic identification of Eumops maurus and Eumops hansae (Chiroptera: Molossidae) with new reports from Central Amazonia - Adrià López-Baucells; Ricardo Rocha; Valéria Da Cunha Tavares; Ligiane Martins Moras; Sara Ema Silva; Paulo Estefano Dineli Bobrowiec; Christoph F.J. Meyer (Tropical Zoology, 2017)
Eumops maurus and Eumops hansae are rarely captured Neotropical molossid bats for which information on taxonomy, natural history, and spatial distribution are scarce. This translates into a poor understanding of their ecology and limits the delimitation of useful characters for their identification. Here, we describe records of these two molossids from the Central Brazilian Amazon, providing data on their external and craniodental morphology, DNA barcode (COI) sequences complemented by acoustic data for the species. Morphological characters, DNA sequence data and phylogenetic relationships within the genus Eumops were consistent with those previously described for both species. Echolocation call characteristics did not differ significantly so as to be useful for separating E. maurus and E. hansae from other congeners. Our records are, respectively the first and the second for Central Amazonia as one individual previously attributed to Eumops amazonicus from Manaus may be considered a junior synonym for E. hansae. These new records increase the extent of the species’ known ranges, partially filling in previous existing gaps in their distribution in central South America. Our data further suggest that these molossid bats forage in a wider range of habitats than previously thought.